Marketing macro environment during the pandemic Covid-19 - Mohammad Haidzir, Humaira; Abu Seman, Noor Aslinda; Harun, Amran (Penerbit UTHM, 2022)
Without a doubt, COVID-19 is indeed a disease caused by a recently discovered coronavirus strain, a form of a virus known to cause human respiratory infections. On January 24, 2020, the first case of Malaysia with COVID-19 was detected. In Malaysia, the World Health Organization (WHO) worked closely with the Ministry of Health to respond to this epidemic. Furthermore, according to the WHO report, as of November 15, 2020, a total of 47,417 COVID-19 confirmed cases have occurred in Malaysia. There have been 23 new deaths recorded in the past week. This brings to 309 the cumulative number of COVID-19 deaths since the epidemic started in Malaysia (WHO, 2020). At the same time, COVID-19 has a significant effect on businesses and the economy and catastrophic cases for people's health. There has never been a more urgent need for companies to reconsider and reconfigure their businesses for a changing environment as the COVID-19 pandemic continues to evolve. It is now time for organizations to concentrate on supporting critical areas of their companies that will help them stabilize and strategize for what is next in the new climate.